Draft Seventh Five Year Plan Andhra Pradesh 1985-90 Volume II Section IX Medical and Public Health - Planning Commission (Planning Commission, 1985)
The outlay for Sixth Five Year Plan (1980-85) for Medical Education and Medical Relief Schemes was Rs. 2500.00 lakh of which Rs. 563.48 was meant for capital works. An amount of Rs. 1129.53 lakhs was spent on Medical Education Schemes. Even though it was proposed to increase 275 new beds in the Teaching Hospitals, Gandhi Hospital Secunderabad was sanctioned 310 beds, E.N.T. 25 beds, M.G.M.
Finance and Planning (Plg. Wing) Department, Government of Andhra Pradesh